A produção da representação social do risco fiscal: um estudo de caso na perspectiva do Posto Fiscal de Estreito - Bomfim Júnior, Wagner de Oliveira (2020)
The Fiscal Risk is a natural result of the activity of the agencies that deal with tax. Nevertheless this subject isn’t quite often analyzed by the social sciences. The economic tools or the political dominates this realm. The neoliberal policies and the crisis of the Tax State are reasons for more research into the fiscal landscape. The focus is usually the small state’s budget but the quest of the tax’s source has been omitted. Therefor this work deals with the tax evasion using ethnographic tools and the concept of social representation from Moscovici to design a new insight of the fiscal situation. The Rio Grande do Sul’s budget situation and the tax oversight are analysed.